Design and Analysis of a New Natural Illumination Device through Lumen Method Approach - ABDUL HAMID, RAHIMAH; YAAKOB, MOHD YUHAZRI; HASOLOAN , HAERY IAN PIETER (Trans Tech Publications, Switzerland, 2013)
The design and development of a natural illumination device (NID) for Malaysian roofing system is explored and improved with the aid of Lumen Method Approach at the analysis stage. The aim of this research is to channel and distribute natural sunlight from exterior to interior building to enlighten the required space in a daytime. It is made up of three main parts; dome as light collector,light tube as light reflector and light diffuser as light distributor. The result shows illuminance level for the NID in full summer sun and overcast summer sun conditions are higher than T8 fluorescent lamp